The mission continues…. (22nd March 2014) - Gamble, Luke
Abstract : In September last year, more than 400 volunteers from 14 different countries set out to vaccinate 50, 000 dogs in India against rabies, as part of a project that ultimately aims to eliminate the disease. Here, Luke Gamble, the driving force behind Mission Rabies, discusses why such initiatives are needed, how the first mass vaccination campaign went and what the goals are for the future